Penilaian Acuan Patokan (PAP) di Perguruan Tinggi : Prinsip dan Operasionalnya - Nurbayani, Etty (Dinamika Ilmu, 2012)
Criterion Referenced Grading (CRG), where grading is determined based on the absolute standard, it is very good or very compatible to be applied in formative tests where lecturers want to find out to what extend the students “have been formed/shaped”. after joining courses in the certain period. CRG is oriented based on success standard or passing grade which is certain. By applying CRG, lecturers can find out number of the students who have high, moderate, and low level of mastery. Therefore, the lecturer can do required efforts to achieve instructional objective optimally.